Ethnicity, vocational education and training and the competition for advancement through education in New Zealand - Strathdee, Rob; Cooper, Grant (Taylor & Francis, 2017)
Reform of vocational education and training policy (VET) in New Zealand has been underpinned by the view that VET can contribute more to equal opportunity by creating more meaningful and rewarding pathways into employment, and by neutralising the influence of background factors on achievement. While the reforms have succeeded in some respects, research shows that participation in VET remains structured by background factors including ethnicity, socio-economic status and gender. This primarily theoretical paper contributes further to the debate by assessing the relationship between ethnicity, participation and achievement in VET, and the labour market. To advance this argument, the research draws upon field theory, which highlights the importance of differences in the rules of the competition for advancement through education across time and space in mediating the outcomes of VET.